Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

Diastereoselective multi-component tandem condensation: synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles - Gupta, Vijay; Sahu, Debashish; Jain, Shailja; Vanka, Kumar; Singh, Ravi P. (Organic & Biomolecular Chemistry, 2019)
A general strategy for a one-pot stereoselective synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles by reaction of salicylaldehyde, malononitrile and butenolides via a tandem Knoevenagel/Pinner/vinylogous Michael condensation is presented. The beta,gamma-butenolides gave a syn-selective MCR adduct with a dr up to 11.5 : 1. The mechanistic insight into the MCR was obtained by DFT calculations.